ANTHELMINTIC ACTIVITY OF MUSA PARADISIACA (L.) CV. PUTTABALE (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Musa paradisiaca cv. Puttabale (AB group) is an indigenous banana cultivar commonly cultivated in the Malnad region of Karnataka, India. Helminthes infections are acute and chronic illness in human beings and cattle. About 3 million people are infected with helminthes worldwide. Traditionally, the plant M. paradisiaca cv. Puttabale was used to expel parasitic worms. In order to justify the ethanomedicinal claim with scientific report, sincere attempts have been made to investigate the Anthelmintic activity from corm ethanol extracts of M. paradisiaca cv. Puttabale using Pheretima posthuma as an experimental model. Three concentrations of 25, 50 and 100 mg/ml of corm ethanol extract were used to study their effect in time of paralysis and death of worm. The results suggest that the ethanol extract at the concentration of 100 mg/ml showed significant effect in time of paralysis at 42.33±1.45 min and death time was 54.00±0.58 min than control group in time of paralysis (142.67±1.45 min) and death (168.00±1.53 min). Standard drug piperazine citrate showed paralysis on 39.67±0.88 min and death at 59.00±0.58 min. The corm ethanol extract confirmed antihelmintic activity in dose depend manure and efficient, than standard drug piperazine citrate. This investigation revealed that the antihelmintic property of ethanol extracts of Musa paradisiaca cv. Puttabale against Pheretima posthuma to support its medicinal claims.